(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
Summary: 1. Pharmaceutical patents, the access to essential medicines and the question of innovation - 2. The actual and/or potential between the rights of inventors, international human rights law, trade rules and public health. The everlasting controversy on the allegedly adverse impact of intellectual property protection on access to medicines and health technologies - 3. Are human rights and intellectual property law really in conflict? A relation of interpretation, not of conflict - 4. Conclusions.